PENGUATAN TECHNOLOGICAL PEDAGOGICAL KNOWLEDGE GURU MADRASAH DI PASURUAN MELALUI PELATIHAN PEMANFAATAN APLIKASI BERBASIS IT - Basori Basori; Harir Mubarok; Nur Fitria Anggrisia; Agwin Degaf (Fakultas Sains dan Teknologi, 2023)
Teachers are required to equip themselves with knowledge about the use of technology in teaching. The purpose of this community service activity is to strengthen technological pedagogical knowledge (TPK) of madrasah teachers through training in the use of a variety of free IT-based applications. The training that is as a form of teacher self-development focused on madrasah teachers in Pasuruan area and MAN 1 Pasuruan was the school where the training was executed. Using the ASSURE model, the training ran well. As indicated from the data resultsed from questionnaire distributed as part of the training evaluation showed positive attitudes, such as the training improved teachers’ motivation in utilizing IT-based applications in teaching, and added references to a variety of free IT applications. The results of monitoring also shows that teachers used the applications for teaching their classes. At the end, the teachers expected that the training on technology related topic should be conducted continuously in the future. Keywords: IT-based Applications, Training, Strengthening TPK